Automated grindstone chemistry: a simple and facile way for PEG-assisted stoichiometry-controlled halogenation of phenols and anilines using N-halosuccinimides - Dharmendra Das; Akhil A. Bhosle; Amrita Chatterjee; Mainak Banerjee (Beilstein Journal of Organic Chemistry, 2022)
A simple electrical mortar–pestle was used for the development of a green and facile mechanochemical route for the catalyst-free halogenation of phenols and anilines via liquid-assisted grinding using PEG-400 as the grinding auxiliary. A series of mono-, di-, and tri-halogenated phenols and anilines was synthesized in good to excellent yields within 10–15 min in a chemoselective manner by controlling the stoichiometry of N-halosuccinimides (NXS, X = Br, I, and Cl). It was observed that PEG-400 plays a key role in controlling the reactivity of the substrates and to afford better regioselectivity. Almost exclusive para-selectivity was observed for the aromatic substrates with free o- and p-positions for mono- and dihalogenations. As known, the decarboxylation (or desulfonation) was observed in the case of salicylic acids and anthranilic acids (or sulfanilic acids) leading to 2,4,6-trihalogenated products when 3 equiv of NXS was used. Simple instrumentation, metal-free approach, cost-effectiveness, atom economy, short reaction time, and mild reaction conditions are a few noticeable merits of this environmentally sustainable mechanochemical protocol.